Pola Pengkaderan Kesatuan Aksi Mahasiswa Muslim Indonesia (KAMMI) dalam Membentuk Kepribadian Muslim di Perguruan Tinggi Se-Kota Palembang - Bobi Sugara; Kasinyo Harto; Rusdy A Siroj (Bahasa Indonesia, Bahasa English, 2019)
KAMMI cadre education process is a process that is continuous and constantly experiencing growth. From a number of trainings attended by KAMMI cadres, there is a tendency and correlation between KAMMI cadre patterns and the religious behavior of participants / cadres. The higher the level of education followed by KAMMI pastors / cadres, the more thought patterns and religious behavior of participants / cadres will be formed as a Muslim person. This research uses descriptive qualitative research methods. The purpose of this research is to find out the pattern of cadre of Kesatuan Aksi Mahasiswa Muslim Indonesia (KAMMI) in universities throughout Palembang in shaping Muslim personalities, to find out their Muslim personalities and to understand the religious behavior of their cadres. The results showed that the KAMMI cadre pattern was oriented to the Cadre Identity Index (IJDK) as a measure to determine the success of the cadre pattern that was carried out and the implementation of the KAMMI cadre pattern in shaping Muslim personalities in direct proportion to the level of cadre membership. Muslim personalities will be formed when KAMMI members / cadres follow the regeneration pattern to the maximum. The pattern of KAMMI cadre formation of Muslim personalities has implications for the cadre's religious behavior. Referring to the understanding of Muslim personality from Hasan Al-banna about muwashofat Muslim personality, that KAMMI cadres in terms of aqidah, worship and morality tend to have reached mowasofat or cadre identity index (IJDK) but in some muwashofat (index) or indicators are still lacking, as in the case of maintaining physical / physical health, expertise and breadth of scientific insight, especially foreign languages and writing scientific papers. In addition, in terms of economic independence, the majority of KAMMI cadres are still not economically independent.